Phytotoxicity of organic extracts of Turnera ulmifolia L. and Turnera diffusa Willd. ex Schult. in cucumber seeds - Silvestre, Daniel Moreto [UNESP]; Kolb, Rosana Marta [UNESP]; Frei, Fernando [UNESP]; Santos, Catarina dos [UNESP] (FapUNIFESP (SciELO), 2013)
We evaluated the phytotoxic effects that the hexane, ethyl acetate and methanol extracts from leaves and branches of the species Turnera ulmifolia L. and Turnera diffusa Willd. ex Schult. (Turneraceae), at concentrations of 1.25, 2.50, 3.75 and 5.00 mg ml-1, have on seed germination and seedling development in cucumber (Cucumis sativus L.). None of the extracts tested prevented germination, although the ethyl acetate extracts of T. diffusa, at 3.75 and 5.00 mg ml-1, reduced the mean germination speed and time to germination. Hexane extracts of both species reduced the main root length, number of secondary roots and hypocotyl length. In the ethyl acetate and methanol extracts, the number of secondary roots and hypocotyl length varied by species and concentration. Ethyl acetate extracts of T. ulmifolia at ≤ 2.50 mg ml-1stimulated growth of the main root and hypocotyl, as did T. ulmifolia methanol extracts at 1.25 and 3.75 mg ml-1; all other extract/concentration combinations had an inhibitory effect on those parameters. The hexane and ethyl acetate extracts of T. diffusa inhibited the formation of secondary roots and of the main root, although significant inhibition of hypocotyl growth was observed only at ≥ 2.50 mg ml-1. Comparatively, T. diffusa extracts inhibited development to a greater degree, thus presenting greater allelopathic potential, than did T. ulmifolia extracts.
Keywords: Allelopathy; Cucumis sativus; Development; Germination